Antihypertensive therapy during pregnancy: the prescription pattern in Italy - Locatelli, Anna; Bellante, Nicolò; Donatiello, Gianluca; Fortinguerra, Filomena; Belleudi, Valeria; Poggi, Francesca R.; Perna, Serena; Trotta, Francesco (Frontiers in Pharmacology, 2024)
Drug use during pregnancy should be evidence-based and favor the safest and most appropriate prescription. The Italian Medicines Agency coordinates a network focusing on monitoring medication use in pregnancy. Hypertensive disorders are common medical complication of pregnancy and antihypertensive therapy is prescribed to reduce the risk of adverse feto-maternal complications. The objective of this study is to highlight the prescription pattern of antihypertensive drugs before pregnancy, during pregnancy and in the postpartum period in Italy and to evaluate their use with a specific attention to the prescription pattern of drugs considered safe during pregnancy. A multi-database cross-sectional population study using a Common Data Model was performed. We selected all women aged 15-49 years living in eight Italian regions who gave birth in hospital between April 1, 2016 and March 31, 2018. In a cohort of 449.012 women, corresponding to 59% of Italian deliveries occurred in the study period, the prevalence of prescription of antihypertensive drugs in the preconceptional period was 1.2 %, in pregnancy 2.0 % and in the postpartum period 2.9 %. Beta-blockers were the most prescribed drugs before pregnancy (0.28-0.30%). Calcium channel blockers were the most prescribed drugs during pregnancy, with a prevalence of 0.23%, 0.33%, 0.75% in each trimester. Alfa-2-adrenergic receptor agonists were the second most prescribed during pregnancy with a prevalence of 0.16%, 0.26% and 0.55% respectively. The prescription of drugs contraindicated during pregnancy was below 0.5%. In general, the prescription of antihypertensive drugs in the Italian Mom-Network is coherent with the drugs compatible with pregnancy.